Vodun Continuum in Black America: Communication with the Dead and the Invisible World in Jesmyn Ward’s Sing Unburied Sing - AZON, Sènakpon Adelphe Fortuné (My University, 2021)
Abstract The spread of Western rationalism through armed conquest, with the global dominance of Judeo-Christian and Islamic creeds, has almost obliterated the existence of the alternative ontological perceptions rooted in the dominated people’s cultures. This essay studies how Ward’s Sing Unburied Sing reaches back to African ancestral beliefs, vodun practices and rituals, and brings to life characters who strive to counteract exclusion with the conception of the world as a Whole, a continuum whose survival is premised on the respect of, and fusional union with, each element of that Whole. This conception partakes in the search for meaning to existence in a society that has erected individualism and the exclusion of black people into creed. The paper uses the theoretical approach of vodun ontology and, in an Afrocentric perspective, reads through Ward’s novel this cultural trait thriving centuries after the enslaved people’s departure from Africa. It purports to voice African traditional values and to celebrate cultural difference.
Keywords: Keywords: vodun; connection; conjuring; ghost; suffering